GFDL SHiELD: A Unified System for Weather‐to‐Seasonal Prediction. (17th October 2020) - Harris, Lucas; Zhou, Linjiong; Lin, Shian‐Jiann; Chen, Jan‐Huey; Chen, Xi; Gao, Kun; Morin, Matthew; Rees, Shannon; Sun, Yongqiang; Tong, Mingjing; Xiang, Baoqiang; Bender, Morris; et al.
Abstract: We present the System for High‐resolution prediction on Earth‐to‐Local Domains (SHiELD), an atmosphere model developed by the Geophysical Fluid Dynamics Laboratory (GFDL) coupling the nonhydrostatic FV3 Dynamical Core to a physics suite originally taken from the Global Forecast System. SHiELD is designed to demonstrate new capabilities within its components, explore new model applications, and to answer scientific questions through these new functionalities. A variety of configurations are presented, including short‐to‐medium‐range and subseasonal‐to‐seasonal prediction, global‐to‐regional convective‐scale hurricane and contiguous U.S. precipitation forecasts, and global cloud‐resolving modeling. Advances within SHiELD can be seamlessly transitioned into other Unified Forecast System or FV3‐based models, including operational implementations of the Unified Forecast System. Continued development of SHiELD has shown improvement upon existing models. The flagship 13‐km SHiELD demonstrates steadily improved large‐scale prediction skill and precipitation prediction skill. SHiELD and the coarser‐resolution S‐SHiELD demonstrate a superior diurnal cycle compared to existing climate models; the latter also demonstrates 28 days of useful prediction skill for the Madden‐Julian Oscillation. The global‐to‐regional nested configurations T‐SHiELD (tropical Atlantic) and C‐SHiELD (contiguous United States) show significant improvement in hurricane structure from a new tracer advection scheme and promise for medium‐range prediction of convective storms. Plain Language Summary: At many weather forecasting centers where computer weather models are run, different models are run for different applications. However, each separate model multiplies the effort needed to maintain and upgrade each model and makes it difficult to move improvements between models. We present a new "unified" weather modeling system, System for High‐resolution prediction on Earth‐to‐Local Domains, able to be configured for a variety of applications. This system uses a powerful computer code, FV3, to compute the fluid motion of the atmosphere at any scale and also able to zoom in on areas of interest to better "see" severe storms or intense hurricanes. We show how we started from a quickly assembled model for testing FV3 and then gradually improved the representation of different atmospheric processes and expanded into new uses for the system, including short‐range severe thunderstorm prediction, hurricane forecasting, and forecasts out to as long as 6 weeks. We address some of the challenges that we faced and discuss prospects for future model improvements. Since many of the parts of System for High‐resolution prediction on Earth‐to‐Local Domains are used by models being developed by the National Weather Service for use by weather forecasters, the advances described here can be rapidly introduced into those models, eventually improving official forecasts. Key Points: A unified "one code, one executable, one workflow" global prediction modeling system is presented SHiELD's multiple configurations show prediction skill and simulation fidelity matching or exceeding those of existing U.S. models The FV3 Dynamical Core provides a powerful foundation for unified prediction modeling